The Effect Of Economic Literacy And Social Media On Student Entrepreneurial Interest - Rofiah, Chusnul; Prasetyo, Deni Widyo; Hidayati, Nurul (Eksis: Jurnal Riset Ekonomi dan Bisnis, 2019)
This study aims to explain the effect of economic literacy and social media on the entrepreneurial interest of STIE PGRI Dewantara Jombang students. This type of research is explanatory research (explanatory research) with a quantitative approach. The population in this study were students of STIE PGRI Dewantara Jombang class of 2016 while the sample of 82 respondents was taken using purposive sampling technique. The data used are primary data obtained through questionnaires and secondary data in the form of documentation and photos. Furthermore, the data is processed using Multiple Linear Regression and T-test to test the hypothesis. The results of the analysis show that there is a significant influence between economic literacy and social media on the entrepreneurial interest of STIE PGRI Dewantara Jombang students in 2016.